Metabolic imaging of fatty kidney in diabesity: validation and dietary intervention. Issue 2 (15th September 2017) - Jonker, Jacqueline T; de Heer, Paul; Engelse, Marten A; van Rossenberg, Evelien H; Klessens, Celine Q F; Baelde, Hans J; Bajema, Ingeborg M; Koopmans, Sietse Jan; Coelho, Paulo G; Streefland, Trea C M; Webb, Andrew G; Dekkers, Ilona A; et al.
Abstract: Background: Obesity and type 2 diabetes have not only been linked to fatty liver, but also to fatty kidney and chronic kidney disease. Since non-invasive tools are lacking to study fatty kidney in clinical studies, we explored agreement between proton magnetic resonance spectroscopy ( 1 H-MRS) and enzymatic assessment of renal triglyceride content (without and with dietary intervention). We further studied the correlation between fatty kidney and fatty liver. Methods: Triglyceride content in the renal cortex was measured by 1 H-MRS on a 7-Tesla scanner in 27 pigs, among which 15 minipigs had been randomized to a 7-month control diet, cafeteria diet (CAF) or CAF with low-dose streptozocin (CAF-S) to induce insulin-independent diabetes. Renal biopsies were taken from corresponding MRS-voxel locations. Additionally, liver biopsies were taken and triglyceride content in all biopsies was measured by enzymatic assay. Results: Renal triglyceride content measured by 1 H-MRS and enzymatic assay correlated positively ( r = 0.86, P < 0.0001). Compared with control diet-fed minipigs, renal triglyceride content was higher in CAF-S-fed minipigs (137 ± 51 nmol/mg protein, mean ± standard error of the mean, P < 0.05), but not in CAF-fed minipigs (60 ± 10 nmol/mg protein) compared with controls (40 ± 6 nmol/mg protein). Triglyceride contents in liver and kidney biopsies were strongly correlated ( r = 0.97, P < 0.001). Conclusions: Non-invasive measurement of renal triglyceride content by 1 H-MRS closely predicts triglyceride content as measured enzymatically in biopsies, and fatty kidney appears to develop parallel to fatty liver. 1 H-MRS may be a valuable tool to explore the role of fatty kidney in obesity and type 2 diabetic nephropathy in humans in vivo .